Celastrol Inhibits the Growth of Ovarian Cancer Cells in vitro and in vivo - Xu, Li-Na; Zhao, Na; Chen, Jin-Yan; Ye, Piao-Piao; Nan, Xing-Wei; Zhou, Hai-Hong; Jiang, Qi-Wei; Yang, Yang; Huang, Jia-Rong; Yuan, Meng-Ling; Xing, Zi-Hao; Wei, Meng-Ning; et al. (Frontiers in Oncology, 2019)
Celastrol is a natural triterpene isolated from the Chinese plant Thunder God Vine with potent antitumor activity. However, the effect of celastrol on the growth of ovarian cancer cells in vitro and in vivo is still unclear. In this study, we found that celastrol induced cell growth inhibition, cell cycle arrest in G2/M phase and apoptosis with the increased intracellular reactive oxygen species (ROS) accumulation in ovarian cancer cells. Pretreatment with ROS scavenger N-acetyl-cysteine totally blocked the apoptosis induced by celastrol. Additionally, celastrol inhibited the growth of ovarian cancer xenografts in nude mice. Altogether, these findings suggest celastrol is a potential therapeutic agent for treating ovarian cancer.